Customer Loyality Segmentation with RFM Model at PCP Cafe - Rahmadeni, Rahmadeni; Heikal, Jerry (CV. ITTC INDONESIA, 2024)
The intense competition in the business sector motivates every business unit to manage their services, especially towards their customers, to the fullest. One of them is to increase customer loyalty by segmenting or grouping each customer into several clusters and determining the appropriate marketing strategy for each of these groups. Loyalty is the tendency of customers to purchase a product or service from a business unit with a high level of consumption consistency. Customer loyalty will become a point of success not only in the short term but also in the long term as a sustainable advantage. In determining the segmentation of loyal customers, a careful and accurate analysis based on the characteristics of each customer in their transactions is necessary. Segmentation or grouping of customers can be done through RFM analysis (Recency, Frequency, and Monetary) using primary customer data, which in this study is the customer data of PCP Cafe. The research results show that there are 3 (three) customer segments, namely non-loyal customers, less loyal customers, and very loyal customers. Disloyal customers are those who frequently move around and do not consistently visit or purchase products. Less loyal customers are those who often come but do not yet fall into the category of loyal customers. Meanwhile, very loyal customers are those who frequently visit and repeatedly purchase products. The results of the segmentation will later serve as the basis for determining the development strategy of the business unit in the future.